How and when corporate social responsibility affects salespeople's organizational citizenship behaviors?: The moderating role of ethics and justice - Castro-González, Sandra; Bande Videla, Belén; Kimura, Takuma (Corporate Social Responsibility and Environmental Management, 2019)
The influence of corporate social responsibility (CSR) on salespeople's organizational citizenship behaviors (OCBs) has been widely neglected by academic literature. This paper analyzes the influence of salespeople's perceived dimensions of CSR on the salespeople OCB through organizational commitment. Additionally, the study proposes that interpersonal justice and ethical climate have a moderate effect on the relationship between CSR and commitment, and consequently, the relationship between CSRs and OCBs. The empirical analysis is based on dyadic data from 176 salespeople and their supervisors from 96 companies. The findings not only confirm the importance of the social, environmental, and economic actions to influence on salespeople OCBs, but also, it reveals unexpected conclusions about moderating variables. In addition, the paper identifies the main implications of these results for management and makes some suggestions for future studies.
Keywords: corporate sustainability; CSR; ethical climate; interactive justice; organizational citizenship behaviors; organizational commitment; JCR; Scopus